1994
DOI: 10.1007/bf02540460
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition ofHerrania andTheobroma seeds

Abstract: The seeds of nineHerrania and nineTheobroma species were surveyed for fatty acid, sterol, tocopherol and tocotrienol compositions. Principal component and cluster analyses suggested that these analytes could be used collectively as chemotaxonomic criteria to differentiate theHerrania species from theTheobroma species, as well as to provide subgroup distinctions within each genus for comparison to the existing classification schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 9 publications
11
19
0
Order By: Relevance
“…The fatty acid compositions of the seed fats from Theobroma and Herrania species (Table 2) were similar to those described in the literature,11–13 considering variations due to genotype, season or environmental effects. The only major exceptions were the data for T microcarpum and H mariae , both sampled from the same collection as used by Carpenter et al 14 The data presented here for T microcarpum were similar to the fatty acid composition of T gileri reported by Chaisieri et al ,23 another species of the section Telmatocarpus. Therefore it is likely that the discrepancy in fatty acid composition for T microcarpum analysed by Carpenter et al 14 might have derived from erroneous identification, pod maturity or postharvest conservation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The fatty acid compositions of the seed fats from Theobroma and Herrania species (Table 2) were similar to those described in the literature,11–13 considering variations due to genotype, season or environmental effects. The only major exceptions were the data for T microcarpum and H mariae , both sampled from the same collection as used by Carpenter et al 14 The data presented here for T microcarpum were similar to the fatty acid composition of T gileri reported by Chaisieri et al ,23 another species of the section Telmatocarpus. Therefore it is likely that the discrepancy in fatty acid composition for T microcarpum analysed by Carpenter et al 14 might have derived from erroneous identification, pod maturity or postharvest conservation.…”
Section: Resultssupporting
confidence: 78%
“…Studies have demonstrated the diversity of Theobroma species for a series of important qualitative characteristics, such as purine alkaloid, fatty acid, tocol and sterol composition in seeds 11–14. Fat from seeds of T grandiflorum (cupuassu) has been particularly investigated15–17 because of its increasing demand as a new fruit crop 18.…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa butter fatty acids and triacylglycerols profiles significantly differ from the seed fats from other Theobroma species (Carpenter et al 1994;Gilabert-Escrivá et al 2002). In general, the fatty acid composition of T. sylvestre and T. speciosum (section Oreanthes) are the most similar to cocoa butter, but both had significantly higher palmitate content and significantly lower stearate.…”
Section: Related Wild Species Of T Cacaomentioning
confidence: 88%
“…Cacao seed cotyledons also contain high levels of polyphenols (14-20% dry weight), which have also been implicated in the formation of specific flavor notes (Afoakwa et al 2008). Seeds from other Theobroma species have been less characterized, but all contain high levels of fat, ranging from around 38% in T. bicolor to 64% in T. obovatum (Carpenter et al 1994), and significant amounts of proteins, ranging from 15 to 28% based on the dry weight of defatted seeds (Silva et al 2001). Seeds of Theobroma species contain less polyphenol than cacao seeds, with values ranging from 0.3% (T. speciosum) to 8% (T. bicolor), while some species, particularly seeds from T. speciosum contain large amounts of polysaccharides in the cotyledons (Martini et al 2008).…”
Section: Related Wild Species Of T Cacaomentioning
confidence: 97%
See 1 more Smart Citation